The association between dietary fiber intake and severe headaches or migraine in US adults - Huang, Hao; He, Kaiyin (Frontiers in Nutrition, 2023)
Background: The data on the effect of dietary fiber on severe headaches or migraine are limited. Therefore, this study aimed to investigate the association between dietary fiber intake and the prevalence of severe headaches or migraine. Methods: We conducted a cross-sectional study involving 12,710 participants, all data collected from NHANES 1999-2004. A multivariable logistic regression model was used to analyze the relationship between dietary fiber intake ( as an independent variable) and severe headaches or migraine (as outcome variable). We also performed sensitivity analyses, including multiple sensitivity analyses. Results: The overall incidence of severe headache or migraine in the study was 2527/12,710 (19.9%). After adjusting for correlation covariates, we found a significant inverse association between dietary fiber intake and severe headache or migraine, with lowest prevalence in the fifth quintile (OR: 0.74, 95% CI: 0.61–0.90). Our study also revealed that for every 10g/d increase in dietary fiber intake, the prevalence of severe headache or migraine decreased by 11%. However, no such inverse association was found among Mexican Americans, other races, or those with a BMI of 25 to 30. E-value analysis suggested robustness to unmeasured confounding. Conclusion: Increasing the intake of fiber-rich foods might protect from severe headache or migraine. More prospective studies should be conducted to confirm their association before dietary recommendations.